Field notes contributed by Francis L. Moore, winter 1983-1984 - Moore, Francis L.et al (1983)
Field notes were contributed by Francis L. Moore, winter 1983-1984. Other observers were Robert K. Myers and Robert Wylder. Species that were documented were Northern Goshawks at Sweet Marsh in Bremer County and at Big Marsh in Butler County, as well as a Pine Grosbeak with no location on the form. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1983-1984. Epson - sheet feed